Strategi Pengembangan Bisnis Pengadaan Barang dan Jasa Berbasis BMC pada CV Samudera Abadi - Deritani Zebua; Musnaini Musnaini (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
CV Samudera Abadi is a company that runs a business in the Procurement of Goods and Services, CV Samudera Abadi was established since 2020 in Paal Lima, Kotabaru Jambi. The purpose of this study is to determine the current conditions experienced by CV Samudera Abadi and recommendations for alternative strategies that are suitable for developing CV Samudera Abadi in the procurement of goods and services and also the sale of goods to partners andcustomers nya, the number of informants in this study was 5 people consisting of, the director of CV Samudera Abadi, the first Admin of CV Samudera Abadi, the second Admin of CV Samudera Abadi, the receptionist of CV Samudera Abadi, and the partner of CV Samudera Abadi, namely from PTPN VI Jambi. The data in this study were obtained using the Triangulation technique and analyzed using the SWOT analysis technique and mapping of 9 elements onBusiness Model Canvas(BMC) to find out what strategy is used as an alternative development strategy. The results of the BMC study show that CV Samudera Abadi has been able to fulfill the 9 elements of BMC but still needs improvement for CV Samudera Abadi to be more advanced, the results of the SWOT study of CV Samudera Abadi show that it is in quadrant III which means that it has weaknesses internally or in the CV Samudera Abadi company itself, therefore there is still a need for a development strategy at CV Samudera Abadi, namely (1) creating a structured management system in the business sector (2) adjusting the products/services offered to be more in line with market needs andcustomer(3) developing new markets (4) improving service quality (5) improving office facilities.